GAMBARAN STATUS KONTROL ASMA DAN KUALITAS HIDUP ANAK DENGAN ASMA DI RSUP PROF. DR. I.G.N.G NGOERAH DENPASAR DAN RSUD WANGAYA DENPASAR TAHUN 2020-2021 - Nurliandari, Nia; Witarini, Komang Ayu; Mayangsari, Ayu Setyorini Mestika; Pratiwi, I Gusti Ayu Putu Eka (E-Jurnal Medika Udayana; Vol 12 No 12 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i12.P03, 2023)
Asthma is a chronic and emergency disease in children. Uncontrolled asthma in children can affect the quality of life of children and even lead to death. Bali is the province with the third highest prevalence of asthma after the Special Region of Yogyakarta and East Kalimantan. However, data regarding the description of asthma control status and quality of life of children with asthma in Bali, especially in Denpasar, are still limited. Therefore, the authors want to know the overview of asthma control status and quality of life of children with asthma at Prof. Dr. I.G.N.G Ngoerah Hospital Denpasar and Wangaya Hospital Denpasar in 2020-2021. The design of this research is descriptive observational with a cross-sectional approach. After the approval of the constitutional ethics committee, all children aged 6-11 years with asthma at the Outpatient and Inpatient Respirology Pediatric Clinic Prof. Dr. I.G.N.G Ngoerah Hospital Denpasar and Wangaya Hospital Denpasar in 2020-2021 which is recorded in a complete medical record and has approval for participation in the study by parents/guardians (n=32) will be given a questionnaire containing the child and parent’s biodata, Childhood Asthma Control Test (C-ACT) to assess asthma control status, and Pediatric Quality of Life (PedsQL) to assess children's quality of life through an electronic form. Based on asthma control status, the results showed that 27 children (84.4%) had fully controlled asthma control status and 5 children (15.6%) had partially controlled asthma control status. In controlled asthma control status, all children were male. The majority of children (3 children) have poor nutritional status and some (2 children) have obese nutritional status. All children have a family history of asthma. Most of the children's parents have the latest education in college (3 children), senior high school (1 child), and elementary school (1 child). All parents of children have jobs and most of them (3 parents of children) have salaries above the minimum wage. Based on the quality of life, there were 4 children (12.5%) with a disturbed quality of life and 28 (87.5%) children with an undisturbed quality of life. In terms of quality of life, there were 2 children, male and female, respectively. The majority of these children had good nutritional status (2 children) and did not have a family history of asthma (3 children). The parents of the 2 children have the last education in elementary school, while the other 2 parents have the last education in college. All of the children's parents have jobs and the majority (3 parents of children) have salaries above the minimum wage. Further research is needed with a larger sample size and should be carried out prospectively so that the data obtained is more complete.